THE INFLUENCES OF AVAILABLE SOIL WATER DEPLETION FRACTION TO GROWTHS AND YIELDS OF THREE SOYBEAN (Glycine Max (L) Merril) VARIETIES - Komang, Ardiyasa (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
The objective of this research was to find out the influences of available soil water depletion fraction to growths and yields of three soybean varieties. This research used a factorial design in a completely randomized design with the first factor was the available soilwater depletion fraction (p), which contained of three treatment levels of (p); they were p1 (p=0.2 AW), p2 (p=0.4 AW), and p3 (p= 0.6 AW). The second factor was soybean varieties containing of three varieties; V1 = Willis, V2 = Kaba, and V3 = Tanggamus, which were repeated three times. Irrigationwas conducted when soil water levels was close to or above threshold of available soilwater depletion whichwas determined bymeasuringwater level at gypsumblock and ohmmeter device. Irrigationwas conducted by returning water level to field capacity condition. Treatment of available soil water depletion fraction for the plants influences soybean in growth phase ofWilis (V1) variety, Kaba (V2) variety and Tanggamus (V3) variety. Observation data frominweek 8 of three showed that the highest stemgrowthwas in Kaba variety (55.87 cm) at p2 treatment (p=0.4 AW). The highest leave amountwas Kaba variety (66.93 leaves) at treatmentp2 (p=0.4 AW). The highest production was in Kaba variety (71.33gr) at treatment p2 (p=0.4 AW). The highest irrigation necessitywas in treatment p2with 18mm water irrigation, and then followed by p3with 13.5mm and finally p1 with 9mm. The lowirrigationwater necessity was influenced by high rainfall level of 578mmwith 32 rainy days during research. Keywords: soybeans,available soilwaterdepletion fraction, gypsumblock